PERLINDUNGAN DANA NASABAH YANG DI SIMPAN DI BANK MENURUT UNDANG-UNDANG NO 24 TAHUN 2004 TENTANG LEMBAGA PENJAMIN SIMPANAN. - Yanuarsi, Susi (Faculty of Law, University of Palembang, 2018)
With the enactment of Law Number 24 of 2004 on deposit insurance institutions, the arrangement of guarantee for the most important to provide legal certainty to depositors of funds at banks, related to the encourages customers to rush or freeze business license of the bank. With the guarantee that it is possible for customers to trust the banking institution, and others that can be used by the deposit insurance institutions.